ANALISIS KEMAMPUAN PENALARAN MATEMATIS SISWA KELAS IV SDN GAYAMSARI 02 DI KOTA SEMARANG - Arianto, Ahmad Subqi; Sulianto, Joko; Azizah, Mira (Jurnal Sinektik, 2019)
The objectives of this study are: (1) Describe the implementation of mathematics learning at Gayamsari 02 Semarang Elementary School (2) Describe the classification of mathematical reasoning abilities of fourth grade students at Gayamsari Elementary School 02 Even Semester 2018/2019. The method used in this study is a qualitative method. Research location at Gayamsari 02 Elementary School Semarang. Data collection is done through observation, questionnaires, interviews and documentation as well as for collecting data on mathematical reasoning abilities of students using test questions. The validity of the data is done by means of triangulation techniques. Based on the data analysis that has been done, mathematics learning is included in the good category with an average score above 3, mathematical reasoning classification data obtained the highest results of 56.41% and the lowest results of 10.25%, it can be concluded that the implementation of mathematics learning at SDN Gayamsari 02 Semarang shows good results, but for the results of tests on mathematical reasoning questions related to students' ability to reason with material in many aspects and flat build is still lacking